Referral Flow for Maternal and Child Health in Central Java Province during Health Crises Management - Handayani, Novia; Sriatmi, Ayun; Martini, Martini; Jati, Sutopo Patria; Kusumawati, Aditya; Budiyono, Budiyono; Armunanto, Armunanto; Friska, Erlin; Asfiya, Nissa Atul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Central Java Province is one of the provinces that often experiences disasters. During the period 1 May 2023 – 31 May 2023, 72 incidents of strong winds, 8 incidents of land moving, 107 incidents of flooding, 94 incidents of landslides, 6 volcanic eruptions, and 2 incidents of fire were recorded. In disaster emergencies, the health needs of mothers and children are often overlooked. This study aims to analyze the flow of maternal and child health referrals in health crisis management in the focus location regencies in Central Java Province. This research is descriptive research with a qualitative approach. Data was collected through Focus Group Discussion (FGD) in March 2023. The research locations were Semarang Regency, Brebes Regency, Grobogan Regency, and Klaten Regency. The sample selection technique used was purposive sampling. The integrated referral system is not yet running optimally. The health referral flow carried out is not yet specialized in treating mothers and children. Pentahelix collaboration is carried out in managing health crises. The supporting factors in disaster management are the existence of policies, the availability of infrastructure for evacuating victims, as well as coordination from various sectors. Meanwhile, the inhibiting factors are the lack of trained human resources, limited logistics, and low public awareness regarding disasters. Thus, there is a need to develop a special referral pathway for maternal and child health involving multi-sectors, increase public awareness of disaster management, and strengthen Pentahelix collaboration in health crisis management.